Perancangan Sistem Informasi Pemesanan Pentas Seni Berbasis Web Pada Sanggar Seni Getar Pakuan Bogor - Taufik, Andi; - STMIK Nusa Mandiri Jakarta, Ermawati (Indonesian Journal on Software Engineering (IJSE), 2017)
Abstract  – In developing and promoting art houses Getar Pakuan Bogor still use manual way as order staging should be coming directly to studio, so that experienced difficulty in it  reservations for customers. Information expected customers more visual and interactive so it is more efficient and appealing to customers looking for information  reservations staging on studio. The author uses the method waterfall mode which includes the  step of the analysis, design, coding, testing,support (support) and maintenance phase(maintenance).  The purpose of this research is develop information systems reservations staging web  based that can be used in doing the service to the customers in providing information on reservations staging so information about obtained customers shaped information systems that can be directly conducted reservations staging onlineKeyword: Information System, Reservations Staging Online. Abstrak- Dalam memajukan dan mempromosikan Sanggar Seni Getar Pakuan Bogor masih menggunakan cara manual seperti memesan pementasan harus datang langsung ke Sanggar, sehingga mengalami kesulitan dalam hal pemesanan bagi pelanggan. Informasi yang diharapkan pelanggan lebih visual dan interaktif sehingga lebih efisien dan menarik bagi pelanggan yang mencari informasi pemesanan pementasan pada sanggar. Penulis menggunakan metode model waterfall yang meliputi tahap analisa, design, pengkodean, pengujian, pendukung (support) dan tahap pemeliharaan(maintenance).  Tujuan penelitian ini adalah membuat sistem informasi pemesanan pementasan berbasis web yang dapat dimanfaatkan dalam melakukan pelayanan kepada pelanggan dalam memberikan informasi pemesanan pementasan sehingga informasi yang diperoleh pelanggan berbentuk sistem informasi yang dapat langsung melakukan pemesanan pementasan secara online.Kata Kunci: Sistem Informasi, pemesanan pentas seni Online.